PENGARUH PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING YANG DIPADUKAN DENGAN TEKNIK CATATAN TULIS DAN SUSUN TERHADAP HASIL BELAJAR MENERAPKAN DASAR-DASAR KELISTRIKAN DAN ELEKTRONIKA KELAS X JURUSAN TEKNIK AUDIO VIDEO SMK NEGERI 5 PADANG - Nadia Utari; Putra Jaya; Hanesman Hanesman (Universitas Negeri Padang, 2014)
The purpose of this study is to know the difference between learning model of quantum teaching that combine with the technic record writing and structure and learning model of direct instruction in learning ouput on Menerapkan Dasar-Dasar Kelistrikan dan Elektronika for grade X TAV of SMK Negeri 5 Padang on odd semester, academic year 2013/2014. This type of research is true experimental. Participant were slected by non-probability sampling technique with purposive sampling. 30 students from Class XE3 TAV, which served as a controling class, used learning model of direct instruction. 30 students from Class XE1 TAV, which served as experimental class, used learning model of quantum teaching that combine with the technic record writing and structure. Data is collected from the final test then was analyzed for homogeneity testing, normality and hypothesis testing. The result indicates that experimental class has mean 78,7, while controlling class has mean 69,7. The result of hypothessis testing on significant level α = 0,05 is 4,887 > 2,042. Since the tcount is higher than the t table, then H0 is rejected and H1 is accepted. It can be inferred that learning model of quantum teaching that combine with the technic record writing and structure is better than learning model of direct instruction.